Online Learning Design to Implement Student Communication Skills - Rochgiyanti Rochgiyanti; Fathurrahman Fathurrahman; Mulyani Safitri; Rhoma Dwi Aria Yuliantri; Akhmad Priyanka Tegar Pangabdi (Edumaspul: Jurnal Pendidikan, 2023)
The purpose of this study is to describe online learning designs in applying students' communication skills. The method used in this research uses descriptive qualitative. Data was obtained through observation, interviews, and documentation. Data analysis refers to Miles and Huberman's interactive data analysis technique, which consists of data collection, data reduction, data presentation, and drawing conclusions. The results of the study show that the teacher's planning for online teaching in history subjects is in accordance with the lesson plans. Then, the RPP made by the teacher contains students' communication skills. The models and methods used by teachers in teaching adapt to the characteristics of students so that learning can run well.